A comparative investigation on tribological properties of piston ring/cylinder liner tribo-pair using GNP and GNF dispersed lubricants. (14th November 2022) - Singh, Gurtej; Wani, M.F.; Wani, M. Marouf
The friction and wear characteristics of piston ring/cylinder liner tribo-pair are investigated using graphene nano-platelets (GNP) and graphite nano-flakes (GNF) as lubricant additives in SAE15W40. The nano-lubricants used for tribological testing comprise 0.1% GNP and 0.1% GNF. The effect of variable loads (100 N-500 N), sliding speed (0.16 m/s-0.8 m/s) and sliding distance (Sd ) of 26 km was evaluated during tribological tests as per ASTMG181 standards. The friction coefficient (COF) and specific wear rate (SWR) reduced with increasing load, sliding speed and Sd for both nano-lubricants in comparison with base oil 15W40. The maximum COF and SWR was observed in the case of base oil and the minimum COF and SWR was observed in the case of 0.1% GNP + 15W40. The COF decreased by 26% and SWR reduced by 24% and 19% for ring and liner respectively using GNP. The oriented layered 2D structure of GNP exhibiting nano-scale super-lubricity properties forming a micro-polished surface was found to be responsible for the maximum reduction in COF and SWR.